PENGUATAN KLINIK MANDI MADU DALAM PENCEGAHAN PTM DI PUSKESMAS JAMBE KABUPATEN TANGERANG TAHUN 2024 - Juniarti, Diana Eka; Subuh, Muhammad (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
Non-communicable diseases (NCDs), particularly diabetes mellitus and hypertension, are major health challenges in Indonesia. The Jambe Community Health Center (Puskesmas Jambe) developed an innovative service model called MANDI MADU as a community-based promotive and preventive effort. This study aims to evaluate the effectiveness of the innovation using the CIPP (Context, Input, Process, Product) evaluation model. This study employed a qualitative approach with an evaluative study design. Data were collected through in-depth interviews, participatory observations, and document reviews. Informants included program implementers, the head of the health center, health cadres, and NCD patients. Thematic analysis and source triangulation were applied to ensure data validity. The evaluation showed that the MANDI MADU program emerged from a strong local contextual need and received internal policy support. However, limitations in human resources and cadre training posed challenges in the input phase. In terms of process, the program was carried out with good coordination and innovative practices. The outcomes included increased patient adherence to treatment, improved health knowledge, and strengthened cadre roles in early detection of NCDs. The success of this innovation was influenced by its alignment with local needs, strong commitment from implementers, and active community involvement. Nonetheless, challenges remain in funding, information system integration, and cadre capacity, which need to be addressed for sustainability. MANDI MADU has proven to be an effective community-based strategy for NCD control. However, its sustainability requires institutional strengthening, improved funding mechanisms, and capacity-building for human resources. The program holds potential for replication in other regions with appropriate local adaptations. ABSTRAKPenyakit Tidak Menular (PTM), khususnya diabetes melitus dan hipertensi, merupakan tantangan kesehatan utama di Indonesia. Puskesmas Jambe mengembangkan inovasi layanan MANDI MADU sebagai upaya promotif-preventif berbasis komunitas. Penelitian ini bertujuan mengevaluasi efektivitas inovasi tersebut menggunakan model evaluasi CIPP (Context, Input, Process, Product). Penelitian ini menggunakan pendekatan kualitatif dengan desain studi evaluatif. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan telaah dokumen. Informan terdiri dari pelaksana program, kepala puskesmas, kader kesehatan, dan pasien PTM. Analisis data dilakukan dengan pendekatan tematik dan triangulasi sumber. Evaluasi menunjukkan bahwa program MANDI MADU lahir dari kebutuhan konteks lokal dan memperoleh dukungan kebijakan internal. Namun, keterbatasan sumber daya manusia dan pelatihan menjadi tantangan pada tahap input. Secara proses, program dijalankan dengan koordinasi yang baik dan inovatif. Dampak program meliputi peningkatan kepatuhan pasien terhadap pengobatan, peningkatan pengetahuan kesehatan, dan penguatan peran kader dalam deteksi dini PTM. Menunjukkan bahwa keberhasilan inovasi ini dipengaruhi oleh relevansi program dengan kebutuhan lokal, komitmen pelaksana, serta keterlibatan aktif masyarakat. Namun, tantangan pada aspek pendanaan, integrasi sistem informasi, dan kapasitas kader perlu ditindaklanjuti. Inovasi MANDI MADU efektif sebagai strategi pengendalian PTM berbasis masyarakat, namun keberlanjutannya memerlukan penguatan kelembagaan, pembiayaan, dan kapasitas SDM. Program ini berpotensi direplikasi ke wilayah lain dengan adaptasi lokal.